Kantowskie foedus pacificum: droga do pokoju czy prolegomena neoliberalizmu i autorytarnej korporacjonistycznej globalizacji we współczesnych liberalnych demokracjach? - Garrett, Terence M. (Annales. Etyka w Życiu Gospodarczym, 2020)
Immanuel Kant’s language and concept of foedus pacificum (league of peace) combined with his call for a spirit of trade promised a prescription for world peace—“seeking to end all wars forever.” Nation-state level cooperation between liberal democracies has borne out Kant’s analysis to some effect. A consequence of the twin pursuits of foedus pacificum and spirit of trade has ironically resulted in the exploitation of society. Today’s international corporations adversely affect public policies ostensibly designed to protect citizens through an anti-democratic market-based ideology within the State—as seen through the lenses of Foucauldian post-structural theory and Debord’s society of the spectacle. The author proposes that globalist-corporatist control of governing apparatuses is now exposed for its authoritarian tendencies. This action could result in the ultimate destruction of the representative democratic state with the onset of neoliberalism and authoritarianism.